2018
DOI: 10.1017/dmp.2018.57
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain is Associated With New-Onset Psychological Distress in Survivors of the Great East Japan Earthquake

Abstract: Musculoskeletal pain is associated with new-onset psychological distress among survivors of the Great East Japan Earthquake. (Disaster Med Public Health Preparedness. 2018;page 1 of 6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The association of musculoskeletal pain with LBP is stronger due to an increased number of pain sites. A high prevalence of musculoskeletal pain was reported after the GEJE, and many survivors experienced pain at multiple sites [17]. This is presumed to be one explanation for our finding of increased LBP after the GEJE.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The association of musculoskeletal pain with LBP is stronger due to an increased number of pain sites. A high prevalence of musculoskeletal pain was reported after the GEJE, and many survivors experienced pain at multiple sites [17]. This is presumed to be one explanation for our finding of increased LBP after the GEJE.…”
Section: Discussionmentioning
confidence: 56%
“…If yes, please place a mark next to all your symptoms." The examples of choices were palpitation, dizziness, diarrhoea, and musculoskeletal symptoms such as low back, hand and/or foot, knee, shoulder, and neck pain [17]. The outcome of interest was new-onset LBP, which was defined as LBP absent at 3 years (first period), and present at 4 years (second period) after the GEJE.…”
Section: Musculoskeletal Painmentioning
confidence: 99%
See 1 more Smart Citation
“…If yes, please place a mark next to all your symptoms." The examples of choices were palpitation, dizziness, diarrhoea, and musculoskeletal symptoms such as low back, hand and/or foot, knee, shoulder, and neck pain [17]. The outcome of interest was new-onset LBP, which was defined as LBP absent at three years (first period), and present at four years (second period) after the GEJE.…”
Section: Musculoskeletal Painmentioning
confidence: 99%
“…Numerous studies have reported on the physical and mental health problems that are observed following natural disasters 4 9–13. Following the GEJE, the development of musculoskeletal (MSK) symptoms, both acute and chronic, has been a major concern among survivors 14.…”
Section: Introductionmentioning
confidence: 99%